Synthesis of hydroxyapatite fibers using electrospinning: A study of phase evolution based on polymer matrix. Issue 6 (June 2020) - Sebastian, T.; Preisker, T.R.; Gorjan, L.; Graule, T.; Aneziris, C.G.; Clemens, F.J.
Abstract: Hydroxyapatite (HA) is considered as the most promising biomaterial candidate to replace and regenerate hard tissues. A small amount of β-tricalcium phosphate (β-TCP) phase is advantageous for rapid bonding of the artificial bones to natural ones due to its high solubility compared to hydroxyapatite. Synthesizing HA nanofibers from electrospinning of sol-gel is considered as a widely researched topic. Motivation of the current work was to investigate the influence of polymeric binder in the final phase evolution after heat treatment of electrospun nanofibers. Calcium phosphate nanofibers were fabricated by electrospinning sols using gelatine and polyvinylpyrrolidone as carrier polymers and subjected to heat treatment. It was realized that carrier polymers facilitate preferential calcium phosphate phase formation by forming hydroxyapatite as major phase while PVP was used and β-TCP with HA as secondary phase while gelatine was employed. XRD and thermal analyses were performed to ascertain the reason behind this interesting behaviour.